2019
DOI: 10.1002/ijop.12649
|View full text |Cite
|
Sign up to set email alerts
|

Neural underpinnings of the relationships between sensation seeking and emotion regulation in adolescents

Abstract: There is little neurological evidence linking sensation seeking and emotion regulation in adolescence, which is characterised as an emotionally fluctuant period. The present study examined the relationship between sensation seeking and emotion regulation in adolescents. Electroencephalograms were recorded from 22 high sensation‐seeking adolescents (HSSs, Mage = 12.36) and 24 low sensation‐seeking adolescents (LSSs, Mage = 12.84) during the reactivity and regulation‐image task. Group differences in event‐relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…Many studies have suggested that ERP indices of emotion regulation are related to modulations in attentional regulatory processes (e.g., P1, N2, P3, and early LPP components related to salience detection, stimulus-driven orientation, and attentional control) and cognitive regulatory processes (e.g., late LPPs related to cognitive control, meaning evaluation, and response modulation) [23][24][25][26].…”
Section: Erp Components Related To Emotion Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have suggested that ERP indices of emotion regulation are related to modulations in attentional regulatory processes (e.g., P1, N2, P3, and early LPP components related to salience detection, stimulus-driven orientation, and attentional control) and cognitive regulatory processes (e.g., late LPPs related to cognitive control, meaning evaluation, and response modulation) [23][24][25][26].…”
Section: Erp Components Related To Emotion Regulationmentioning
confidence: 99%
“…The late positive potential (LPP) is evident as a broad superior posterior positive signal that occurs approximately 300 to 400 ms after stimulus onset [22]. In most studies of LPP, researchers divided this positive slow wave into different time windows and examined the average amplitude of the LPP within the relatively long time window [22,26,32]. The LPP reflects the facilitated attention to emotional stimuli; that is, it is not only sensitive to emotional stimulation itself but its time course is also an indicator of the emotion regulation process [33].…”
Section: Erp Components Related To Emotion Regulationmentioning
confidence: 99%
“…Research has shown that people who are high in sensation seeking, such as shopaholics, exhibit weaker self‐regulation and more limited strategies for regulating their emotions than normal people (Williams & Grisham, 2012). People with high sensation seeking were more responsive to emotional stimuli and had weaker cognitive control in emotional regulation in an electroencephalogram experiment (Deng & Zhang, 2020). Some researchers postulated that the stronger the emotional responsiveness of individuals, the more difficult it is for them to regulate their emotions; that is, individuals with high emotional responsiveness are more likely to have difficulty regulating their emotions (Nock et al., 2008).…”
Section: Introductionmentioning
confidence: 99%